LA VARIABILITE PLUVIOMETRIQUE ET SES IMPACTS SUR L’ALIMENTATION EN EAU DES MILIEUX RURAUX DU DEPARTEMENT DE DIMBOKRO (CENTRE-EST DE LA COTE D’IVOIRE) - Jérôme Aloco N’guessan; Yoboue Kouadio Bernard; N’daoule Remi (European Scientific Journal, ESJ, 2015)
Rainfall variability in the tropics is a real living reality. In Côte d'Ivoire in general and the Department Dimbokro in particular takes this variability increasingly growing. It is increasingly felt on the forest-savanna contact zone climate and weather conditions are already difficult. This study's main objective is to analyze the rainfall and temperature data over a long period to determine the various trends, breaks in series, then to bring out the consequences for the supply of various rural communities in water department. Clearly it is to characterize the climate event from the analysis of air temperature, relative humidity, changes in rainfall index, the frequency of rainy days and seasons of life rainfall over the period 1955-2000 in order to identify the behavior of seasonal rainfall patterns in the context of climate variability. The analysis of these different climate components including rainfall data, thermal have identified two broad periods separated by a hinge year 1968. Climate variability is manifested by a spatiotemporal dynamics regressive annual rainfall, recession frequency of rainy days in general and especially those of rainfall amounts in excess of 20 mm. Such climatic situation has huge consequences for the availability of hydrology department. The reservoirs in the geological layers will be insufficiently fed, and thereby show their inability to supply boreholes and wells. Once this water recession creates a situation of water stress in the entire department. And 20.57% of the holes drilled in the department have proven nonoperational. It therefore concludes that rainfall variability that knows the department has real impacts on the water supply to rural communities in Dimbokro department.